Automotive steering, suspension, and alignment - Halderman, James D. 1943- (Prentice Hall, 1995)
Today's automotive repair industry demands knowledge of diagnostic procedures and skill development as never before. Focusing primarily on problem diagnosis, this clear and concise book is packed with examples of practical technical information, ideas, tips, and detailed service techniques. Reflects the authors' extensive practical experience, covering all essential topics but weeding out extraneous information. Provides Tech Tips throughout in easy-to-read sidebars that give hints to solving real-life service problems. Includes Diagnostic Stories that explore real problems and solutions in detail. Includes full-color photo sequences with detailed captions to explain concepts and operations; also available on video. Features an accompanying multimedia CDROM with sound, animation, color photo sequences with voice, ASE task list for the ASE exam, and much more